Wound healing and fibrosis: current stem cell therapies. (8th February 2019) - Jones, Ruth Ellen; Foster, Deshka S.; Hu, Michael S.; Longaker, Michael T.
Abstract : Scarring is a result of the wound healing response and causes tissue dysfunction after injury. This process is readily evident in the skin, but also occurs internally across organ systems in the form of fibrosis. Stem cells are crucial to the innate tissue healing response and, as such, present a possible modality to therapeutically promote regenerative healing while minimizing scaring. In this review, the cellular basis of scaring and fibrosis is examined. Current stem cell therapies under exploration for skin wound healing and internal organ fibrosis are discussed. While most therapeutic approaches rely on the direct application of progenitor‐type cells to injured tissue to promote healing, novel strategies to manipulate the scarring response are also presented. As our understanding of developmental and stem cell biology continues to increase, therapies to encourage regeneration of healthy functional tissue after damage secondary to injury or disease will continue to expand.